The dysregulation of the immune microenvironment during endometrial intraepithelial neoplasia serves as a marker of endometrial carcinogenesis - Peng, Yingying; Zhong, Guanglei; Zhou, Minqi; Yao, Yuwei; Dong, Kejun; Yang, Zheng; An, Lanfen; Zhang, Jun; Zhang, Jiarui; Zhang, Shuo; Tang, Qianqian; Wang, Hongbo (Frontiers in Immunology, 2026)
The development of endometrial cancer is a gradual malignant transformation process driven by multiple factors, and the immune microenvironment is closely related to clinical outcomes and immunotherapy responses. Under physiological conditions, the immune microenvironment of the normal endometrium undergoes periodic reshaping under the regulation of estrogen and progesterone, maintaining the balance between immune defense and reproductive capacity. However, continuous exposure to risk factors, such as non-antagonistic estrogen, may trigger endometrial intraepithelial neoplasia. During this period, the immune microenvironment becomes dysregulated, supporting malignant progression. For example, estrogen-stimulated interactions between endothelial cells and macrophages, elevated neutrophil/lymphocyte ratios, and the accumulation of regulatory T cells all combine to cause dysregulation of immune microenvironment. The abnormal immune microenvironment that occurs in the precancerous lesion stage interacts with systemic and genetic carcinogenic factors, ultimately shaping the unique immune microenvironment of each molecular subtype of endometrial cancer. POLE-mutated and MSI-H subtype endometrial cancer are immune-infiltrated tumors, whereas the copy-number high subtype is immune-suppressive tumor and the copy-number low subtype is immune-desert tumor. However, still little is known about the immune dysregulation that occurs during the precancerous stage and its impact on subsequent malignant progression. This review systematically describes the changes in the immune microenvironment during the process from normal endometrium to endometrial cancer, emphasizing that endometrial intraepithelial neoplasia is a key stage of immune imbalance, thus paving the way for early immune intervention and precise immunotherapy.